Oxygen Vacancies on Hydrated Anatase (101) Surfaces: Insights from Classical and Ab Initio Molecular Dynamics Simulations - Fredrik Grote; Alexander Lyubartsev (Nanomaterials)
Hydrated anatase (101) titanium dioxide surfaces with oxygen vacancies have been studied using a combination of classical and ab initio molecular dynamics simulations. The reactivity of surface oxygen vacancies was investigated using ab initio calculations, showing that water molecules quickly adsorb to oxygen vacancy sites upon hydration. The oxygen vacancy then quickly reacts with the adsorbed water, forming a protonated bridging oxygen atom at the vacancy site and at a neighboring oxygen bridge. Ab initio simulations also revealed that this occurs via a short-lived hydronium ion intermediate. It was investigated how this reaction affects the structure and dynamics of water near the anatase surface. Classical molecular dynamics simulations of surfaces with and without oxygen vacancies showed that vacancies disrupt the second solvation shell, consisting of water molecules hydrogen bonded to the surface, thereby changing the local water density and diffusion as well as the binding modes for hydrogen bonding. Our findings support the hydroxylation of oxygen vacancies on anatase (101) surfaces, rather than stabilization by molecular adsorption or subsurface diffusion. The work gives new atomistic insight into water structure and surface chemistry on the catalytically relevant anatase (101) titanium dioxide surface.